Prevalence of COVID-19 Vaccine Hesitancy Among Healthcare Workers in Nigeria: A Systematic Review and Meta-Analysis - Taagbara Jolly Abaate; Dabota Yvonne Buowari; Utchay A. Agiri; Tamunodiepiriye Inimgba; Vivian Ifeoma Ogbonna; Chizaram Onyeaghala; Glory Ovunda Worgu; Abiye Somiari; Emmanuella I. Ezebuiro; Ibe Arthur Onuah (International Journal of Public Health)
ObjectiveThe purpose of this systematic review and meta-analysis was to determine the prevalence of COVID-19 vaccine hesitancy among Nigerian healthcare professionals.MethodsAn extensive language-unrestricted literature search was conducted across PubMed, Scopus, the Cochrane Library, and the African Index Medicus to identify studies reporting hesitancy to COVID-19 vaccines among healthcare workers in Nigeria. Quality assessment was performed using the Newcastle-Ottawa scale for cross-sectional studies. A single-arm meta-analysis was performed using a random-effects model.ResultsOf the 206 articles, 22 publications with 20,724 participants were included. The pooled prevalence of COVID-19 vaccine hesitancy was 75% (95% CI: 61%–88%, I2 = 99.69%, P < 0.001). Reasons for hesitancy, including concerns about side effects, lack of trust, and safety, were prevalent at 76% (CI: 0.57–0.94, I2 = 99.24%, P < 0.001), 55% (CI: 0.042–0.272, I2 = 97.42%, P < 0.001), and 68% (CI: 0.047–0.89, I2 = 98.59%, P < 0.001), respectively.ConclusionThere was significant hesitancy among Nigerian healthcare workers towards COVID-19 vaccination; thus, strategies to increase vaccination acceptance among healthcare workers should be developed.